FDI patters of interational hotel chains - Santos, M-C.; Brochado, A.; Esperança, J. (GIKA 2016, 2016)
Main issues analysed: - The hotel industry is a typical illustration of the location boundedness. – Simultaneity of production and consumption characterize the service sector. – One of the most heavily globalized industries. – In this study, we focus on a largely internationalized hotel group – Accor – to analyze the location pattern selected by the most active foreign investor among the largest world hotel chains. Our contribution to the existing literature is three fold: we incorporate the predictions of the gravitational model, a powerful tool in the context of foreign trade, but scarcely used for FDI decisions; cultural proximity is tested through the role of language proximity based on the “open circuit” data collected by Melitz (2008); finally we extend the conventional analytical tools by using the Miles and Snow typology using fuzzy set qualitative comparative analysis.